Kilconnell Franciscan Friary, north chancel wall, tomb niche, mullion - O'Donovan, Danielle (My University, 2008)
Mullion of tracery in canopied tomb niche. Moulding comprises: central fillet flanked at either side by hollow, quadrant, right-angled rebate, quadrant, hollow.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Tracery (Architecture); Late Medieval; moldings, hollow; roll moldings; mullions